A comparative LCA study on aluminum electrolytic capacitors: From liquid-state electrolyte, solid-state polymer to their hybrid. (15th November 2022) - Zhang, Cheng; Zheng, Yu; Jing, Junfeng; Liu, Yun; Huang, Haihong
Abstract: Polymer hybrid aluminum electrolytic capacitors (PHAECs) are a new generation of aluminum electrolytic capacitors (AECs) following traditional liquid AECs (LAECs) and polymer AECs (PAECs). The differences in the potential environmental impact among the three types of AECs have not been well investigated. A cradle-to-grave comparative LCA study was conducted to evaluate whether PHAECs have ecologically environmental advantages over PAECs and LAECs throughout their entire life cycle. In this study, the functional unit was taken to be 1, 000, 000 pieces of the AECs with 25 V rated working voltage and 150 μF rated capacitance, each operating for 2000 h. Furthermore, a capacitor manufacturer (located in Jiangsu, China) with its suppliers was investigated to obtain the life cycle inventory data of the AECs. According to the ReCiPe2016 method, climate change, fossil depletion, and photochemical ozone formation were identified as the main categories of AECs' environmental problems. Electricity consumption and aluminum ingot use were identified as the main contributors to AECs' environmental impact based on the ReCiPe2016 normalization factors (mid-point, World). The application of conductive polymer increases the environmental impact of the AECs from cradle to gate but effectively reduces their equivalent series resistance (ESR). In addition, the liquid electrolyte in PHAEC will solve the problem of large leakage currents in PAECs. The environmental impact of PHAECs from cradle to grave, thus, is no more than 30.5% of LAECs and 50.5% of PAECs, respectively. Difference analysis, sensitivity analysis, scenario analysis, and sustainability opportunities of PHAECs were also discussed. This work would provide a quantitative benchmark and calculation framework to assess the environmental burden of the PHAECs and guide environmentally conscious design, manufacturing, marketing, operation, and recycling of future PHAEC products. Graphical abstract: Image 1 Highlights: A comparative analysis of aluminum electrolytic capacitors (AECs) is presented. Polymer hybrid AECs (PHAECs) apply solid conductive polymer with liquid electrolyte. Key impact categories and contributors of AECs are identified based on ReCiPe 2016. PHAECs have obvious environmental advantages over liquid AECs and polymer AECs. The study is beneficial to the sustainable development of future PHAEC products.